1981
DOI: 10.1002/pssb.2221050216
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Compton Profile of Beryllium

Abstract: Starting from a pseudopotential calculation for h.c.p. beryllium the (Jompton profiles are cal- (100) und (1 10) werden durch weitgehende Einbeziehung der O r t h o g o n a l i t l i t k t u r e n verbessert.Es wird eine bemerkenswert grol3e Anisotropie fur I(o01) -I(l02) bzw. I(00l) -1 < 1 1 2 ) gefunden.Der Beitrag des Korrelationsschwanzes in der Impulsverteilung wird abgeschitzt. Beim Vergleich mit Messungen hoher Auflosung mu0 die Korrelation beriicksichtigt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…A few theoretical works which proceed along similar lines as our present work deserve to be mentioned: The pseudopotential calculations of Compton profiles in beryllium, 4 the Hartree-Fock calculations on LiH and BN, 5,6 the works on graphite and intercalation compounds, 7-9 still another pseudopotential calculation on BN, 10 and finally our previous work on LiH within the Hartree-Fock theory and in the basis of Wannier-type functions. 11 A more extensive review can be found, e.g., in Ref.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…A few theoretical works which proceed along similar lines as our present work deserve to be mentioned: The pseudopotential calculations of Compton profiles in beryllium, 4 the Hartree-Fock calculations on LiH and BN, 5,6 the works on graphite and intercalation compounds, 7-9 still another pseudopotential calculation on BN, 10 and finally our previous work on LiH within the Hartree-Fock theory and in the basis of Wannier-type functions. 11 A more extensive review can be found, e.g., in Ref.…”
Section: Introductionmentioning
confidence: 72%
“…͑3͔͒, we apply, as already done in the Ref. 4, the Gramm-Schmidt orthogonalization, which becomes particularly simple when only two functions are dealt with:…”
Section: B the Orthogonalization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…where G's are reciprocal lattice vectors, the directional profile can be written as [10] The summation G is over all the reciprocal lattice vectors where the C" k(G) is non-negligible. The number of G's required to achieve convergence is related to the size of the primitive unit cell and also increases with the hardness of pseudopotentials.…”
Section: Investigation Of Electronic Density In C60 By Compton Scattementioning
confidence: 99%
“…Thereby the Compton profile of the valence electrons can be written as an integral over the Brillouin zone or its irreducible part (1/24) [ 8 ] . This integration was done by an interpolation in a mesh of 222 k-points using the tetrahedron method of Lehmann and Taut [9].…”
Section: Theorymentioning
confidence: 99%